The transformation process of a former industrial plant into an industrial heritage tourist site as open innovation - Mateusz Naramski; Krzysztof Herman; Adam R. Szromek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The study focused on the application of Open Innovations (OI) in industrial heritage tourist sites. The transformation of a former industrial plant into a tourist attraction is one of the most effective ways of heritage preservation. However the process of revitalization can take years or even decades, and guidelines set from experienced facilities that have already gone this path could be extremely valuable for regions aspiring to hold such sites in the future. The benefits would be mutual if the OI had an Outbound Pecuniary structure. Therefore the main goal of our study was to recognize the attitude of industrial heritage sites towards the concept of OI and sharing their experiences regarding revitalization and their business models. For this purpose, a survey was conducted on European Route of Industrial Heritage (ERIH) members. The results that were received from 70 sites show that a vast majority of the subjects are open to the idea of OI with no limitations coming from the type of ownership they have, nor from the sector a recipient of OI would be from. The benefits gained from OI to ERIH sites could have a potentially significant impact on their future development.
Keywords: 650; ERIH; industrial heritage; open innovations; tourism; transformation